Legal Persons and Arrangements ML Risk Assessment Tool : With Guidance on Assessing Risks Related to Beneficial Ownership Transparency - World Bank (Washington, DC : World Bank, 2022)
Legal structures are used to conduct a wide range of legitimate commercial activities and play an essential role in the global economy. In most countries, companies and other forms of legal structures can be formed easily and quickly and can gain access to the global financial system through setting up a corporate bank account, taking out corporate loans, and using other financial products. Through anti-money laundering (AML) and anti-financial crime regulatory reforms, anonymous personal bank accounts are no longer widely available, and so-called ‘shell banks’ that do not have any physical presence in any jurisdiction have been effectively outlawed. Instead, shell companies and other forms of legal structures (such as limited liability partnerships) have emerged as a primary mechanism for moving large amounts of illicit funds around the world. Corporations were originally established to shield individuals from personal liability when conducting business; they were never designed or intended to conceal ownership. But beginning in the 1970s, some offshore jurisdictions began offering to establish corporations and other legal structures that would enable individuals to open bank accounts, transfer funds, and take other actions while hiding their identities. There are four aspects of shell companies and other types of legal structures that are particularly important in the anti-money laundering/combating the financing of terrorism (AML/CFT) context: (1) separate legal personality, (2) hiding ultimate beneficial ownership, (3) providing access to the financial system, and (4) enabling asset ownership.